Molecular Analysis of Turkish Maroteaux-Lamy Patients and Identification of One Novel Mutation in the Arylsulfatase B (ARSB)Gene - ELÇİOĞLU, HURİYE NURSEL (SPRINGER-VERLAG BERLIN, 2014)
Mucopolysaccharidosis type VI (MPS VI, Maroteaux-Lamy syndrome) is an autosomal recessive disorder caused by the deficit of the arylsulfatase B (ARSB) enzyme, which leads to dermatan sulfate pathological storage, resulting in a wide spectrum of clinical phenotypes. To date more than 130 different mutations were reported, most of them being restricted to individual families. We here report the first study on the ARSB gene mutations in MPS VI patients of Turkish ethnogeographic origin. On the whole we analyzed 13 unrelated families recruited from 3 different Turkish clinical centers, for a total of 52 subjects, including patients, parents, and siblings. The molecular characterization of ARSB gene in these subjects lead to the identification of eight different mutations (6 missense mutations and two single-nucleotide deletions) one of which novel: c.532C>G (p.H178D). We characterized seven different genotypes, all homozygous except one. The analysis highlighted c.962T>C (p.L321P) as the most frequently detected mutation in the group of patients examined and the c.1072G>A (p.V358M) as the most frequent polymorphism. All parents and 50% of the healthy siblings analyzed carried in a heterozygous condition the mutation identified in the affected relative. The high number of homozygotes reported in this study reflects the high degree of consanguinity of the Turkish population, being the parents of most of the patients here examined, first-degree cousins. As consanguineous marriages are an integral part of the Turkish society, carriers identification accompanied by genetic counseling in families at risk is the eligible approach to minimize the effects of consanguinity in this population.
Keywords: MUCOPOLYSACCHARIDOSIS TYPE-VI; CLINICAL PHENOTYPE; GENE; N-ACETYLGALACTOSAMINE-4-SULFATASE; TURKEY; FORM; LOCALIZATION; THERAPY; ALLELES; ARSB